Fibre Bragg grating sensors for plantar pressure monitoring at different walking speeds. (1st January 2014) - Suresh, Rupali; Singh, Charandeep; Hao, Jianzhong; Anand, Sneh
This paper presents Fibre Bragg Grating (FBG) sensors for plantar pressure monitoring during walking. For sensors fabrication, the FBGs are embedded within arc shaped layers of carbon composite material. This arc shape embedding technique shows average pressure sensitivity and resolution of 1.3 pm/kPa and 0.8 kPa, respectively. Two such sensors are attached at the sole of a ready to wear shoe at the locations of forefoot and hind foot. Pressure is monitored during various walking speeds. Higher rate of increase in the pressure is observed at the forefoot area as compared to heel when walking speed is increased. The result shows the feasibility of FBG-based compact sensor system for plantar pressure monitoring.